Design of a Solar Tracker for Monitoring Smart Farming Hydroponics Based on the Internet of Things - Isa Rosita; Sufiana Sufiana; Muhammad Safii (Politeknik Pertanian Negeri Samarinda, 2023)
The use of Internet of Things (IoT) technology in agriculture is growing rapidly. One of the IoT technologies that can be utilized in agriculture is smart farming. Smart farming is an agricultural method that uses information and communication technology to increase productivity and efficiency in the agricultural sector, one of which is hydroponics. Hydroponics is a farming technique without using soil media, which uses water as a medium for plant growth. However, in the application of smart farming Hydroponics, some obstacles still need to be overcome. One of these obstacles is plant monitoring which is still done manually, requiring a lot of time and effort. In addition, energy use is also a problem in smart farming Hydroponics applications. One solution to these obstacles is using a solar tracker to monitor smart farming hydroponics. A solar tracker is a technology used to follow the movement of the sun to increase energy efficiency. By using a solar tracker, maximum energy can be generated, so that it can be used for monitoring smart farming hydroponics.